Transcriptional and antagonistic responses of Pseudomonas fluorescens Pf0-1 to phylogenetically different bacterial competitors - Garbeva, Paolina; Silby, Mark W; Raaijmakers, Jos M; Levy, Stuart B; Boer, Wietse de (The ISME Journal, 2011)
The ability of soil bacteria to successfully compete with a range of other microbial species is crucial for their growth and survival in the nutrient-limited soil environment. In the present work, we studied the behavior and transcriptional responses of soil-inhabiting Pseudomonas fluorescens strain Pf0-1 on nutrient-poor agar to confrontation with strains of three phylogenetically different bacterial genera, that is, Bacillus , Brevundimonas and Pedobacter . Competition for nutrients was apparent as all three bacterial genera had a negative effect on the density of P. fluorescens Pf0-1; this effect was most strong during the interaction with Bacillus . Microarray-based analyses indicated strong differences in the transcriptional responses of Pf0-1 to the different competitors. There was higher similarity in the gene expression response of P. fluorescens Pf0-1 to the Gram-negative bacteria as compared with the Gram-positive strain. The Gram-negative strains did also trigger the production of an unknown broad-spectrum antibiotic in Pf0-1. More detailed analysis indicated that expression of specific Pf0-1 genes involved in signal transduction and secondary metabolite production was strongly affected by the competitors’ identity, suggesting that Pf0-1 can distinguish among different competitors and fine-tune its competitive strategies. The results presented here demonstrate that P. fluorescens Pf0-1 shows a species-specific transcriptional and metabolic response to bacterial competitors and provide new leads in the identification of specific cues in bacteria–bacteria interactions and of novel competitive strategies, antimicrobial traits and genes.